Social capital in cooperatives: An evolutionary Luhmannian perspective - Vladislav Valentinov; Constantine Iliopoulos (Journal of Evolutionary Economics, 2021)
In a recent contribution to this journal, Deng et al. (2021) draw on an extensive range of theoretical and empirical literature to make the case for the tendency of social capital resources of agricultural cooperatives in the Western world to decline over time. The present paper revisits this argument by drawing on a Luhmannian systems-theoretic perspective that takes the capitalist economic system to be limitedly sensitive and receptive to a broad variety of human needs. Whereas many of these needs remain marginalized and neglected, some of them may be codified or translated into a profit-making calculus. Cooperatives are shown to present one of the channels through which this codification may be possible; namely, the codification effect of cooperatives enables the incorporation of a multitude of mutual self-help activities into the economic system. This incorporation gives rise to intrasystemic adjustment processes that can be considered complete when the mutual self-help activities introduced by cooperatives no longer require the cooperative form and are integrated into the activities of investor-owned firms. If this view is accepted, then declining social capital may be an indicator of the successful codification process, which helps to make the economic system less exclusionary and more sensitive to human needs.
Keywords: D02; L29; P00; 330; cooperatives; Niklas Luhmann; systems theory